The Impact of Service Quality on Loyalty through Satisfaction as a Mediating Variable - Katarina Neva; Adrie Frans Assa (Al-Qalam Institue, 2025)
This study aims to analyze the influence of service quality and waiting time on patient loyalty at the Emergency Department (ED), with patient satisfaction as a mediating variable. A quantitative method was employed using a survey approach with questionnaires distributed to 100 patients who had visited the ED more than twice. Data were analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach via SmartPLS 4.0. The results show that service quality has a significant positive effect on patient satisfaction and loyalty, while waiting time has a significant negative effect. Additionally, patient satisfaction is proven to be a mediating variable between service quality and waiting time on patient loyalty. These findings suggest that improving service quality and reducing delays can enhance student satisfaction and loyalty in educational settings. Educational leaders can apply these insights to streamline administrative processes, prioritize student needs, and foster a supportive learning environment, ultimately improving student retention and academic outcomes.